Implementasi Sistem Smart Parking Berbasis Internet of Things Di Gedung Parkir Klandasan Kota Balikpapan - Kango, Riklan; ihsan, ihsan; Amsal, Andi Yasir (Jurnal Ilmu Komputer (JUIK), 2023)
Parking space management in metropolitan settings has become more difficult as a result of increased urbanization. To increase parking effectiveness, technological solutions like the Internet of Things (IoT) have been suggested. However, further research is still needed to fully understand the application of IoT in parking systems. This study focuses on the deployment of an Internet of Things-based smart parking system in Balikpapan City's Klandasan Parking Building. Our objective is to increase the effectiveness of parking use and eliminate the frequent parking spot shortage. In the Klandasan Parking Lot, we design and deploy an Internet of Things-based smart parking system. We evaluate the accuracy of infrared sensors, system response time, and parking efficiency before and after system implementation. The findings of our one-week test indicate that the smart parking system can accurately (with 100% sensor accuracy) and quickly (with an average reaction time of 7 miliseconds) detect parking availability. Additionally, the online application gives consumers another level of ease when it comes to getting data about parking availability and making payments. The findings of this study significantly advance our understanding of how IoT is being implemented in parking systems. As a result of this study, it may be possible to apply comparable ideas to urban parking issues on a larger scale